Prey for the devil [videorecording (DVD)] - Zappia, Robert; Jones, Todd R.; Jones, Earl Richey; Barr, Nathan; Byers, Jacqueline, 1996-; Salmon, Colin; Navarro, Christian, 1991-; Palfrey, Lisa; Ralph, Nicholas, 1990-; Taylor, Posy; Cross, Ben; Madsen, Virginia, 1961- (Lionsgate, 2023)
The Roman Catholic Church combats a global rise in demonic possessions by reopening schools to train priests to perform exorcisms. Although nuns are forbidden to perform this ritual, a professor recognizes Sister Ann's gifts and agrees to train her. Thrust onto the spiritual frontline, she soon finds herself in a battle for the soul of a young girl who's possessed by the same demon that tormented her own mother years earlier.